Sulfonate retarder as well as preparation method and application thereof
By designing a structurally optimized sulfonate retarder, the problem of insufficient temperature resistance and hydrolysis resistance of polymer retarders in the prior art under ultra-high temperature and strong alkaline environments is solved, and higher stability and retarding performance are achieved, meeting the safety and quality requirements of ultra-deep well cementing construction.
Patent Information
- Application Number
- CN202411843194.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing polymer oil well cement retarder has insufficient temperature resistance and hydrolysis resistance under ultra-high temperature and strong alkaline environments, resulting in abnormal thickening of cement slurry, affecting the safety and quality of cement construction.
A sulfonate retarder was designed to remove amide groups in its molecular structure, retain sulfonic acid groups, and introduce a temperature-resistant ring structure and carboxylic acid group. It was prepared by specific synthetic methods to improve its stability and retarding performance in high temperature and strong alkaline environments.
This sulfonate retarder shows higher stability and hydrolysis resistance in high temperature and strong alkaline environments, avoids abnormal thickening of cement slurry, meets the needs of ultra-deep well cementing construction, and has good application prospects.
Smart Images

Figure CN119661777A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil wells, and in particular to a sulfonate retarder and a preparation method and application thereof. Background Art
[0002] As oil exploration and development continues to move deeper into deep and ultra-deep wells, the ultra-high temperature at the bottom of the well and the strong alkalinity of the cement slurry pose severe challenges to polymer oil well cement retarders. For example, the CS1 well in the Sichuan Basin is 8,420 meters deep, with a bottom-hole circulation temperature of 200°C; the TK1 well in the Tarim Oilfield is more than 10,000 meters deep, with a bottom-hole circulation temperature of more than 220°C; therefore, improving the temperature resistance of polymer retarders and their anti-hydrolysis ability under strong alkaline conditions is the key to ensuring that retarders play an effective role in ultra-high temperature cementing construction. Among the most commonly used polymer retarders today, AMPS is the most common sulfonate monomer (amide sulfonate), and the amide group will hydrolyze under strong alkalinity and high temperature. When the temperature exceeds 150°C, the high temperature and the strong alkaline environment of the cement slurry will cause the amide group in the side chain of the AMPS retarder to hydrolyze, and as the temperature and the alkalinity of the cement slurry gradually increase, the hydrolysis limit in AMPS will gradually increase, causing the adsorption of sulfonates in the AMPS retarder to be converted to carboxylates in this process, which will lead to abnormal thickening of the cement slurry and bulging of the thickening curve. In particular, the abnormal thickening of cement slurry shared with other AMPS oil well cement admixtures will intensify and lead to cementing construction accidents and affect the cementing quality. Poor temperature resistance and poor hydrolysis resistance under strong alkaline conditions are the technical bottlenecks for the use of AMPS retarders in ultra-high temperature cementing conditions.
[0003] At present, the commonly used non-amide sulfonate monomers are mainly sodium methacrylate sulfonate and sodium p-styrene sulfonate. Sodium methacrylate sulfonate is more sensitive to temperature changes, and its retarding effect fluctuates relatively greatly under different temperature conditions, so it is almost not used as a retarder monomer; while sodium p-styrene sulfonate has relatively higher temperature resistance and is easy to polymerize, but because its sulfonic acid group is too close to the benzene ring, due to the influence of steric hindrance, its inhibitory effect on cement hydration reaction is relatively weak, and higher parameters are required to achieve the same effect as other sulfonates. Under the same dosage, the retarder effect of sodium p-styrene sulfonate as the sulfonate monomer is worse, and it is easy to cause abnormal gelation of cement slurry under high temperature environment. Summary of the invention
[0004] In order to solve the above technical problems, embodiments of the present invention provide a sulfonate retarder and a preparation method and application thereof.
[0005] To achieve the above object, the embodiments of the present invention adopt the following technical solutions:
[0006] In one aspect, the present invention provides a sulfonate retarder having the structural formula shown below:
[0007]
[0008] Among them, X is 16-23, Y is 6-11, and Z is 2-6.
[0009] In another aspect, the present invention provides a method for preparing a sulfonate retarder, comprising the following steps:
[0010] A. Dissolve sodium bisulfite and sodium sulfite in deionized water, add epichlorohydrin to react, and then filter, wash and dry to obtain a sulfonate intermediate;
[0011] The reaction mechanism of the sulfonate intermediate is as follows:
[0012]
[0013] B. dissolving the sulfonate intermediate and vinyl imidazole in deionized water for reaction, then adding anhydrous sodium carbonate to continue the reaction, removing the solvent after the reaction, and purifying to obtain the sulfonate monomer;
[0014] The reaction mechanism of sulfonate monomers is as follows:
[0015]
[0016] C. Under nitrogen atmosphere, sulfonate monomer and itaconic acid are dissolved in deionized water, and the pH value is adjusted to 3-5. Then, 1-allyl-3-methylimidazole chloride and an initiator are added dropwise to the system to react, thereby obtaining a sulfonate retarder.
[0017] Among them, the polymerization reaction mechanism of sulfonate retarder is as follows:
[0018]
[0019] In some embodiments, in step A, the mass ratio of sodium bisulfite, sodium sulfite and epichlorohydrin is (40-65): (15-22): (40-60).
[0020] In some embodiments, in step A, the reaction temperature is 0-10° C., and the reaction time is 8-16 h.
[0021] In some embodiments, in step B, the mass ratio of the sulfonate intermediate, vinylimidazole and anhydrous sodium carbonate is (30-40): (10-20): (4-8).
[0022] In some embodiments, in step B, the reaction temperature of the sulfonate intermediate and vinyl imidazole is 50-70° C., the reaction time is 1-2 h, and the reaction time of the anhydrous sodium carbonate is 8-16 h.
[0023] In some embodiments, in step C, the mass ratio of the sulfonate monomer, itaconic acid, 1-allyl-3-methylimidazole chloride and initiator is (70-100): (20-40): (5-15): (1-4).
[0024] In some embodiments, in step C, the initiator is ammonium persulfate, the reaction temperature is 60-89° C., and the reaction time is 12-24 h.
[0025] In another aspect, the present invention also provides use of the above-mentioned sulfonate retarder or the sulfonate retarder prepared by the above-mentioned preparation method in oil well cement.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention aims at the problem that amide sulfonates (such as AMPS) are hydrolyzed under the combined action of strong alkalinity and high temperature (temperature exceeding 150°C) to cause abnormal thickening of cement slurry, as well as the problem that other non-amide sulfonates are too sensitive to temperature or have poor retarding effect.
[0028] The high temperature resistance, hydrolysis resistance under strong alkaline conditions and retarding properties of sulfonate retarders are closely related to their molecular structure. Therefore, when designing sulfonate monomers, the amide group is removed, the sulfonic acid group with retarding properties is retained, and a heat-resistant cyclic structure is introduced, and the sulfonic acid group is extended to increase the degree of freedom of the sulfonic acid group, thereby improving the retarding properties of the sulfonate monomer. At the same time, the carboxylic acid group and the cyclic cationic group are introduced into the retarder molecule to improve the retarding properties of the retarder.
[0029] That is, a sulfonate intermediate is first prepared by a ring-opening reaction of sodium bisulfite and epichlorohydrin, and then the sulfonate intermediate is quaternized with vinyl imidazole to prepare a sulfonate monomer, and then the synthesized sulfonate monomer, carboxylate monomer (itaconic acid), and cyclic cationic monomer are reacted by aqueous solution free radicals to prepare a sulfonate retarder, and the temperature resistance of the sulfonate retarder can be adjusted by the addition of the sulfonate monomer and the cyclic cationic monomer, and the retarding performance can be adjusted by the addition of the sulfonate monomer and the carboxylate monomer, which has the following specific effects:
[0030] (1) The sulfonate monomer in the present invention uses imidazole as the basic skeleton and does not have an amide group. It will not be hydrolyzed in a high temperature alkaline environment. Compared with AMPS, it has higher stability and hydrolysis resistance, and improves the hydrolysis resistance of the polymer retarder under high temperature and strong alkaline conditions;
[0031] (2) The sulfonic acid group in the sulfonate monomer of the present invention is far away from the five-membered ring. Unlike conventional cyclic sulfonates, the adsorption capacity of the sulfonic acid group is less affected by the ring steric hindrance effect, and its retarding performance is stronger than that of conventional cyclic sulfonates.
[0032] (3) The five-membered ring cation and the carboxylic acid group introduced in the present invention constitute a zwitterionic retarder. Since the retarder itself has a ring structure and the steric hindrance is large near the main chain, the retarder molecule is not easy to curl itself and consume its own charge, and is more effectively combined with the cement hydration product.
[0033] (4) The sulfonate retarder of the present invention benefits from the improvement of the heat resistance and hydrolysis resistance of the sulfonate monomer, while also ensuring the original retarding performance. It is suitable for ultra-deep well cementing process, meets extreme cementing construction requirements, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The infrared spectra of the sulfonate intermediate (SZ-1), the sulfonate monomer (SD-1) and the sulfonate retarder A of the present invention;
[0035] Figure 2 This is the infrared spectrum of poly SD-1 after being treated at a high temperature of 160°C and a pH of 12 in a strong alkaline environment for 5 hours;
[0036] Figure 3 This is the infrared spectrum of polyAMPS after being treated at a high temperature of 160°C and a pH of 12 in a strong alkaline environment for 5 hours;
[0037] Figure 4 This is a comparison chart of the adsorption amount of retarder A and retarder DA on the surface of cement particles;
[0038] Figure 5 This is the thickening curve of the retarder A prepared in Example 1 at 220°C and 145MPa;
[0039] Figure 6 This is the thickening curve of the retarder DA prepared in Comparative Example 1 at 220°C and 145MPa;
[0040] Figure 7 This is the thickening curve of the retarder DB prepared in Comparative Example 2 at 220°C and 145MPa;
[0041] Figure 8 This is the thickening curve of the retarder DC prepared in Comparative Example 3 at 220°C and 145MPa. DETAILED DESCRIPTION
[0042] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.
[0043] Example 1
[0044] (1) Weigh 65 g of sodium bisulfite and 22 g of sodium sulfite, dissolve them in 250 mL of deionized water, and transfer them to a reaction vessel equipped with a stirrer. Maintain the temperature of the reaction system at 5° C. At the same time, weigh 50 g of epichlorohydrin, dropwise add epichlorohydrin to the reaction vessel, and react at a constant temperature for 16 hours to precipitate a white product. The product is filtered and washed with ethanol, then dried and ground to obtain a sulfonate intermediate (denoted as SZ-1).
[0045] (2) Weigh 30 g of the sulfonate intermediate (denoted as SZ-1) and 16 g of vinyl imidazole, dissolve them in 150 mL of deionized water, and transfer them to a reaction vessel with a stirrer. After the temperature of the reaction system rises to 70° C., react at this constant temperature for 2 h. Then weigh 6 g of anhydrous sodium carbonate and add it to the reaction system. Continue to react at this constant temperature for 12 h to obtain a golden yellow solution. The solution after the reaction is desolventized in a rotary evaporator, purified with ice ethanol, and dried at 40° C. to obtain a sulfonate monomer (denoted as SD-1).
[0046] (3) Weigh 70 g of sulfonate monomer (SD-1) and 35 g of itaconic acid and dissolve them in 300 mL of deionized water. Use 20% NaOH solution to adjust the pH value of the solution to 4, then transfer it to a reaction vessel with a stirrer and react under a nitrogen atmosphere; weigh 5 g of 1-allyl-3-methylimidazole chloride and 2 g of ammonium persulfate and dissolve them in 20 mL of deionized water respectively. When the system temperature rises to 80°C, start to drop 1-allyl-3-methylimidazole chloride and ammonium persulfate at the same time, and react at a constant temperature for 16 hours to obtain a polymer retarder, which is recorded as retarder A.
[0047] Example 2
[0048] (1) Weigh 40 g of sodium bisulfite and 15 g of sodium sulfite, dissolve them in 250 mL of deionized water, and transfer them to a reaction vessel equipped with a stirrer. Maintain the temperature of the reaction system at 3° C. At the same time, weigh 40 g of epichlorohydrin, dropwise add epichlorohydrin to the reaction vessel, and react at a constant temperature for 8 h to precipitate a white product. The product is filtered and washed with ethanol, then dried and ground to obtain a sulfonate intermediate (denoted as SZ-2).
[0049] (2) Weigh 40 g of the sulfonate intermediate (SZ-2) and 10 g of vinyl imidazole, dissolve them in 200 mL of deionized water, and transfer them to a reaction vessel with a stirrer. After the temperature of the reaction system rises to 50° C., react at this constant temperature for 1 hour. Then weigh 4 g of anhydrous sodium carbonate and add it to the reaction system. Continue to react at this constant temperature for 8 hours to obtain a golden yellow solution. The solvent is removed from the solution after the reaction in a rotary evaporator, and the solution is purified with ice ethanol and dried at 40° C. to obtain a sulfonate monomer (referred to as SD-2).
[0050] (3) Weigh 100 g of sulfonate monomer (SD-2) and 20 g of itaconic acid and dissolve them in 350 mL of deionized water. Use 20% NaOH solution to adjust the pH value of the solution to 3, then transfer it to a reaction vessel with a stirrer and react under a nitrogen atmosphere; weigh 10 g of 1-allyl-3-methylimidazole chloride and 1 g of ammonium persulfate and dissolve them in 20 mL of deionized water respectively. When the system temperature rises to 60°C, start to drop 1-allyl-3-methylimidazole chloride and ammonium persulfate at the same time, and react at a constant temperature for 24 hours to obtain a polymer retarder, which is recorded as retarder B.
[0051] Example 3
[0052] (1) Weigh 50 g of sodium bisulfite and 17 g of sodium sulfite, dissolve them in 220 mL of deionized water, and transfer them to a reaction vessel equipped with a stirrer. Maintain the temperature of the reaction system at 6° C. At the same time, weigh 60 g of epichlorohydrin, dropwise add epichlorohydrin to the reaction vessel, and react at a constant temperature for 12 h to precipitate a white product. The product is filtered and washed with ethanol, then dried and ground to obtain a sulfonate intermediate (denoted as SZ-3).
[0053] (2) Weigh 35 g of the sulfonate intermediate (SZ-3) and 20 g of vinyl imidazole, dissolve them in 240 mL of deionized water, and transfer them to a reaction vessel with a stirrer. After the temperature of the reaction system rises to 60° C., react at this constant temperature for 2 h. Then weigh 8 g of anhydrous sodium carbonate and add it to the reaction system. Continue to react at this constant temperature for 16 h to obtain a golden yellow solution. The solution after the reaction is desolventized in a rotary evaporator, purified with ice ethanol, and dried at 40° C. to obtain a sulfonate monomer (referred to as SD-3).
[0054] (3) Weigh 80 g of sulfonate monomer (SD-3) and 30 g of itaconic acid and dissolve them in 400 mL of deionized water. Use 20% NaOH solution to adjust the pH value of the solution to 5, then transfer it to a reaction vessel with a stirrer and react under a nitrogen atmosphere; weigh 15 g of 1-allyl-3-methylimidazole chloride and 3 g of ammonium persulfate and dissolve them in 40 mL of deionized water respectively. When the system temperature rises to 70°C, start to drop 1-allyl-3-methylimidazole chloride and ammonium persulfate at the same time, and react at a constant temperature for 18 hours to obtain a polymer retarder, which is recorded as retarder C.
[0055] Example 4
[0056] (1) Weigh 60 g of sodium bisulfite and 20 g of sodium sulfite, dissolve them in 260 mL of deionized water, and transfer them to a reaction vessel with a stirrer. Maintain the temperature of the reaction system at 8° C. At the same time, weigh 60 g of epichlorohydrin, dropwise add epichlorohydrin to the reaction vessel, and react at a constant temperature for 14 hours to precipitate a white product. The product is filtered and washed with ethanol, then dried and ground to obtain a sulfonate intermediate (denoted as SZ-4).
[0057] (2) Weigh 35 g of the sulfonate intermediate (SZ-4) and 14 g of vinyl imidazole, dissolve them in 250 mL of deionized water, and transfer them to a reaction vessel with a stirrer. After the temperature of the reaction system rises to 55° C., react at this constant temperature for 2 h. Then weigh 6 g of anhydrous sodium carbonate and add it to the reaction system. Continue to react at this constant temperature for 14 h to obtain a golden yellow solution. The solution after the reaction is desolventized in a rotary evaporator, purified with ice ethanol, and dried at 40° C. to obtain a sulfonate monomer (referred to as SD-4).
[0058] (3) Weigh 90 g of sulfonate monomer (SD-4) and 40 g of itaconic acid, dissolve them in 420 mL of deionized water, adjust the solution pH to 5 with 20% NaOH solution, and then transfer them to a reaction vessel with a stirrer to react under a nitrogen atmosphere; weigh 5 g of 1-allyl-3-methylimidazole chloride and 1 g of ammonium persulfate, dissolve them in 30 mL of deionized water respectively, wait until the system temperature rises to 60°C, start to drop 1-allyl-3-methylimidazole chloride and ammonium persulfate at the same time, and react at a constant temperature for 16 hours to obtain a polymer retarder, which is recorded as retarder D.
[0059] Example 5
[0060] (1) Weigh 45 g of sodium bisulfite and 19 g of sodium sulfite, dissolve them in 210 mL of deionized water, and transfer them to a reaction vessel with a stirrer. Maintain the temperature of the reaction system at 5° C. At the same time, weigh 55 g of epichlorohydrin, dropwise add epichlorohydrin to the reaction vessel, and react at a constant temperature for 10 hours to precipitate a white product. The product is filtered and washed with ethanol, then dried and ground to obtain a sulfonate intermediate (denoted as SZ-5).
[0061] (2) Weigh 30 g of the sulfonate intermediate (SZ-5) and 18 g of vinyl imidazole, dissolve them in 200 mL of deionized water, and transfer them to a reaction vessel with a stirrer. After the temperature of the reaction system rises to 65° C., react at this constant temperature for 2 h. Then weigh 7 g of anhydrous sodium carbonate and add it to the reaction system. Continue to react at this constant temperature for 10 h to obtain a golden yellow solution. The solution after the reaction is desolventized in a rotary evaporator, purified with ice ethanol, and dried at 40° C. to obtain a sulfonate monomer (referred to as SD-5).
[0062] (3) Weigh 80 g of sulfonate monomer (SD-5) and 25 g of itaconic acid and dissolve them in 400 mL of deionized water. Use 20% NaOH solution to adjust the pH value of the solution to 4, then transfer it to a reaction vessel with a stirrer and react under a nitrogen atmosphere; weigh 10 g of 1-allyl-3-methylimidazole chloride and 2 g of ammonium persulfate and dissolve them in deionized water respectively. When the system temperature rises to 70°C, start to drop 1-allyl-3-methylimidazole chloride and ammonium persulfate at the same time, and react at a constant temperature for 12 hours to obtain a polymer retarder, which is recorded as retarder E.
[0063] Example 6
[0064] (1) Weigh 55 g of sodium bisulfite and 17 g of sodium sulfite, dissolve them in 230 mL of deionized water, and transfer them to a reaction vessel equipped with a stirrer. Maintain the temperature of the reaction system at 2° C. At the same time, weigh 45 g of epichlorohydrin, dropwise add epichlorohydrin to the reaction vessel, and react at a constant temperature for 12 h to precipitate a white product. The product is filtered and washed with ethanol, then dried and ground to obtain a sulfonate intermediate (denoted as SZ-6).
[0065] (2) Weigh 40 g of the sulfonate intermediate (SZ-6) and 12 g of vinyl imidazole, dissolve them in 230 mL of deionized water, and transfer them to a reaction vessel with a stirrer. After the temperature of the reaction system rises to 65° C., react at this constant temperature for 2 h. Then weigh 5 g of anhydrous sodium carbonate and add it to the reaction system. Continue to react at this constant temperature for 12 h to obtain a golden yellow solution. The solvent of the solution after the reaction is removed in a rotary evaporator, and the solution is purified with ice ethanol and dried at 40° C. to obtain a sulfonate monomer (referred to as SD-6).
[0066] (3) Weigh 100 g of sulfonate monomer (SD-6) and 30 g of itaconic acid and dissolve them in 450 mL of deionized water. Use 20% NaOH solution to adjust the pH value of the solution to 3, then transfer it to a reaction vessel with a stirrer and react under a nitrogen atmosphere; weigh 15 g of 1-allyl-3-methylimidazole chloride and 4 g of ammonium persulfate and dissolve them in deionized water respectively. When the system temperature rises to 80°C, start to drop 1-allyl-3-methylimidazole chloride and ammonium persulfate at the same time, and react at a constant temperature for 20 hours to obtain a polymer retarder, which is recorded as retarder F.
[0067] Comparative Example 1
[0068] The SD-1 in Example 1 was replaced by AMPS, and other conditions remained unchanged to obtain a polymer retarder, which was recorded as retarder DA.
[0069] Comparative Example 2
[0070] The SD-1 in Example 1 was replaced with sodium methacrylate sulfonate, and other conditions remained unchanged to obtain a polymer retarder, which was recorded as retarder DB.
[0071] Comparative Example 3
[0072] The SD-1 in Example 1 was replaced with sodium p-styrene sulfonate, and other conditions remained unchanged to obtain a polymer retarder, which was recorded as retarder DC.
[0073] Based on GB / T 19139 oil well cement test method, cement slurry was prepared according to the formula of Experimental Example 1, and cement slurry thickening experiment was carried out under the conditions of circulating temperature of 220°C and 145MPa. The experimental results are shown in Table 1.
[0074] Experimental Example 1
[0075] Formula 1#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 60.75g of retarder A + 255.15g of water;
[0076] Formula 2#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 60.75g of retarder B + 255.15g of water;
[0077] Formula 3#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 60.75g of retarder C + 255.15g of water;
[0078] Formula 4#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 60.75g of retarder D + 255.15g of water;
[0079] Formula 5#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 60.75g of retarder E + 255.15g of water;
[0080] Formula 6#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 0.75g of retarder F6 + 255.15g of water;
[0081] Formula 7#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 60.75g of retarder DA + 255.15g of water;
[0082] Formula 8#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 60.75g of retarder DB + 255.15g of water;
[0083] Formula 9#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 60.75g of retarder DC + 255.15g of water;
[0084] Table 1 Cement slurry thickening performance test results
[0085]
[0086] Note: The bulge in the table refers to the abnormal gelation of cement slurry, which leads to the thickening of cement slurry; the size of the bulge refers to the abnormal gelation of cement slurry and the change value of the cement slurry consistency.
[0087] According to the experimental results of formula 1# and formula 7# in Table 1, it can be concluded that when retarder A and retarder DA are added to the same cement slurry system and under the same cement slurry thickening experimental conditions, the initial viscosity of the cement slurry is low, which meets the requirements of cementing construction. However, the cement slurry thickening curve of the retarder DA group has a bulge of 20Bc near 150°C. This is because the amide group in the sulfonate monomer (AMPS) in DA undergoes hydrolysis reaction under high temperature and strong alkalinity of the cement slurry, while the sulfonate monomer (SD-1) in retarder A does not contain an amide group and has a rigid group, which has stronger heat resistance and hydrolysis resistance. It can maintain good retarding performance in high temperature and strong alkaline environment and will not cause abnormal gelation of the cement slurry.
[0088] According to the experimental results of formula 1# and formula 8# in Table 1, it can be concluded that the retarding performance and temperature resistance of retarder A are better than those of retarder DB. This is mainly because the sulfonate monomer (SD-1) in retarder A has better temperature resistance than sodium methyl methacrylate sulfonate. Therefore, SD-1 can better adapt to the high-temperature cementing construction environment.
[0089] According to the experimental results of formula 1# and formula 9 in Table 1, it can be concluded that although the temperature resistance of retarder DC after replacing SD-1 with sodium p-styrene sulfonate is improved, it has a greater impact on the consistency of cement slurry. The initial viscosity of cement slurry reaches 35Bc, while the initial viscosity of retarder A group is 26Bc, which is much lower and meets the requirements of cementing construction (initial viscosity of cement slurry <30Bc). It can be seen from the thickening time of formula 1# and formula 9# that under the same dosage and the same thickening experimental conditions, retarder A group has a longer thickening time and a better retarding effect.
[0090] from Figure 5-Figure 8 The following conclusions can be drawn from the thickening curve: Figure 5 This is the thickening curve corresponding to retarder A. The sulfonate monomer (SD-1) synthesized using the sulfonate monomer has a stable thickening curve without bulging, and the initial viscosity of the cement slurry is moderate. Figure 6 The thickening curve of retarder DA is shown in Figure 1. The sulfonate monomer used is AMPS. A 20Bc bulge appears at 150°C, which will cause abnormal gelation of cement slurry. Figure 7 This is the thickening curve corresponding to retarder DB. The sulfonate monomer used is sodium methacrylate sulfonate. From the thickening curve, it can be seen that sodium methacrylate sulfonate is very sensitive to temperature and the thickening curve fluctuates greatly. Figure 8 is the thickening curve corresponding to retarder DC. The sulfonate monomer used is sodium p-styrene sulfonate, which has good thickening performance. However, the initial viscosity of the cement slurry is high, reaching 35Bc, and at the same dosage, the thickening time is shorter than that of retarder A. Overall, the retarder corresponding to the sulfonate synthesized in the present invention has excellent retarding performance, temperature resistance and hydrolysis resistance.
[0091] Experimental Example 2
[0092] The retarder A in Example 1 was used to conduct an experiment on the effect of different addition amounts on the thickening performance of cement slurry. The thickening test results are shown in Table 2.
[0093] Formula 1#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 60.75g of retarder A + 255.15g of water;
[0094] Formula 10#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 50.63g of retarder A + 265.28g of water;
[0095] Formula 11#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 40.5g of retarder A + 275.4g of water;
[0096] Formula 12#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 30.28g of retarder A + 285.53g of water;
[0097] Formula 13#: 600g of G-grade oil well cement + 210g of silica fume + 40.5g of fluid loss reducer (AMPS type fluid loss reducer) + 20.25g of retarder A + 295.65g of water;
[0098] Table 2 Thickening performance at different cycle temperatures
[0099] serial number Cycle temperature ℃ Retarder dosage g Thickening time min Recipe 1 220 60.75 319 Recipe 10 220 50.63 294 Recipe 11 220 40.50 265 Recipe 12 220 30.28 238 Recipe 13 220 20.25 206
[0100] It can be seen from Formula 1 and Formulas 10 to 13 in Table 2 that when the circulation temperature remains unchanged, the thickening time of the cement slurry can be adjusted by adjusting retarder A, and the thickening time changes linearly with the amount of retarder added. It can be seen that retarder A has excellent setting performance at 220°C.
[0101] Experimental Example 3
[0102] Weigh 10 g of (SD-1), 40 mL of deionized water, and 0.5 g of ammonium persulfate, and react for 24 h under a nitrogen atmosphere to obtain poly SD-1. The pH value of the poly SD-1 solution after the reaction was adjusted to 12 with sodium hydroxide, and recorded as solution A.
[0103] Weigh 10 g of AMPS, 40 mL of deionized water, and 0.5 g of ammonium persulfate, and react for 24 h under a nitrogen atmosphere to obtain poly-AMPS. The pH value of the poly-AMPS solution after the reaction was adjusted to 12 with sodium hydroxide and recorded as solution B.
[0104] The above-mentioned strong alkaline solution A containing poly SD-1 and the strong alkaline solution B containing poly AMPS were respectively placed in a high temperature resistant polytetrafluoroethylene container and transferred to an aging tank. They were heated in a roller furnace at 160°C for 5 hours. After the end, they were naturally cooled. Parts of solution A and solution B were taken out for drying and ground into powder to make samples SD-1-A and AMPS-B. The two samples were tested by infrared spectroscopy. The results were as shown in Figure 2 and Figure 3 shown.
[0105] contrast Figure 2 SD-1-A and Figure 1 From the infrared spectrum of SD-1, we can see that except for the change of C=C, there is almost no other change, which shows that SD-1 has excellent anti-hydrolysis ability in high temperature and strong alkaline environment. Figure 3 It can be seen that after high temperature and strong alkali treatment, the polyAMPS showed C=O characteristic peak and -OH characteristic peak in the carboxyl group, and the CN bond in the amide group almost disappeared, which once again proved that AMPS was hydrolyzed under high temperature and strong alkaline environment. The specific hydrolysis process is as follows:
[0106]
[0107] Experimental Example 4
[0108] The adsorption of retarder A and retarder DC on cement particles was tested by the following method. The steps are as follows:
[0109] First, prepare retarder solutions of different concentrations, then take 100g of cement and 500ml of retarder solutions of different concentrations to prepare cement slurry, stir the prepared cement slurry at 90℃ for 20min in a normal pressure thickener, then pour it into a high-temperature dehydration instrument and heat it to 160℃, finally apply 3.5MPa pressure at the top and 0.5MPa pressure at the bottom to squeeze out the filtrate. The filtrate is filtered through a filter membrane with a pore size of 0.45μm to obtain a clear filtrate, then diluted 50 times, and then the total organic carbon in the test filtrate is measured by a water environment carbon and nitrogen comprehensive determination instrument (TOC), and the adsorption amount is calculated by the following formula:
[0110]
[0111] Where: γ is the amount of retarder adsorbed on unit cement (mg / g), C1 is the detection concentration (g / L), C0 is the initial concentration of the retarder solution (g / L), M is the mass of cement used (g), and V is the volume of the retarder solution used (mL).
[0112] Table 3 Comparison of adsorption of different concentrations of retarder A and retarder DA on the cement particle surface
[0113]
[0114]
[0115] From Table 3 and Figure 4It can be seen that the adsorption amount of retarder A on cement particles is higher than that of retarder DC at all concentrations. The main reason is that compared with sodium p-styrene sulfonate, the sulfonic acid group in the sulfonate monomer SD-1 in retarder A is far away from the five-membered ring, and the adsorption behavior is less affected by the steric hindrance of the five-membered ring. The sulfonic acid of sodium p-styrene sulfonate is directly connected to the benzene ring, and its adsorption is greatly affected by the steric hindrance of the benzene ring. SD-1 ensures its temperature resistance while improving its ability to bind with cement particles and cement hydration products, and has better retarding performance.
[0116] In summary, the novel sulfonate retarder of the present invention can be applied to high-temperature and strongly alkaline environments, and the cement slurry has a low initial viscosity, a smooth thickening curve, no bulging, and a right-angle thickening. The thickening time is linearly adjustable with the amount of retarder added, thereby ensuring the safe pumping of cement slurry during ultra-deep well cementing construction.
[0117] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.
[0118] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A sulfonate retarder, characterized in that: It has the following structural formula: Among them, X is 16-23, Y is 6-11, and Z is 2-6.
2. A method for preparing a sulfonate retarder as claimed in claim 1, characterized in that: The following steps are involved: A. Dissolve sodium bisulfite and sodium sulfite in deionized water, add epichlorohydrin to react, and then filter, wash and dry to obtain a sulfonate intermediate; B. dissolving the sulfonate intermediate and vinyl imidazole in deionized water for reaction, then adding anhydrous sodium carbonate to continue the reaction, removing the solvent after the reaction, and purifying to obtain the sulfonate monomer; C. Under nitrogen atmosphere, sulfonate monomer and itaconic acid are dissolved in deionized water, and the pH value is adjusted to 3-5. Then, 1-allyl-3-methylimidazole chloride and an initiator are added dropwise to the system to react, thereby obtaining a sulfonate retarder.
3. The preparation method according to claim 2, characterized in that: In step A, the mass ratio of sodium bisulfite, sodium sulfite and epichlorohydrin is (40-65):(15-22):(40-60).
4. The preparation method according to claim 2, characterized in that: In step A, the reaction temperature is 0-10° C., and the reaction time is 8-16 hours.
5. The preparation method according to claim 2, characterized in that: In step B, the mass ratio of the sulfonate intermediate, vinylimidazole and anhydrous sodium carbonate is (30-40):(10-20):(4-8).
6. The preparation method according to claim 2, characterized in that: In step B, the reaction temperature of the sulfonate intermediate and vinylimidazole is 50-70° C., the reaction time is 1-2 hours, and the reaction time of the anhydrous sodium carbonate is 8-16 hours.
7. The preparation method according to claim 2, characterized in that: In step C, the mass ratio of the sulfonate monomer, itaconic acid, 1-allyl-3-methylimidazole chloride and initiator is (70-100): (20-40): (5-15): (1-4).
8. The preparation method according to claim 2, characterized in that: In step C, the initiator is ammonium persulfate, the reaction temperature is 60-89° C., and the reaction time is 12-24 hours.
9. Use of a sulfonate retarder as claimed in claim 1 or a sulfonate retarder prepared by the preparation method of claims 2 to 8 in oil well cement.
Citation Information
Patent Citations
High-temperature-resistant oil well cement retarder and preparation method thereof
CN111253519A
Polymer, ultrahigh-temperature oil well cement retarder and preparation method and application thereof, and cement paste
CN116948095A
MY104007A